2014
DOI: 10.1155/2014/391420
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Plug-Assisted Retrograde Transvenous Obliteration of Portosystemic Shunts for Refractory Hepatic Encephalopathy: A Case Report

Abstract: While balloon-assisted retrograde transvenous obliteration (BRTO) has been used for two decades in Asia for the management of gastric variceal bleeding, it is still an emerging therapy elsewhere. Given the shunt closure brought about by the procedure, BRTO has also been used for the management of portosystemic encephalopathy with promising results. Modified versions of BRTO have been developed, including plug-assisted retrograde transvenous obliteration (PARTO), where a vascular plug is deployed within a porto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…For BRTO, PARTO, and CARTO, clinical success ranges from 91 to 100%, 90.6 to 100%, and 100%, respectively. 2,4,24,[27][28][29]31,38,39 Kim et al detected similar clinical success rates (defined as lack of variceal enhancement on postprocedural CT and cessation of bleeding on endoscopy) between BRTO with EO (93.9%) or STS (92%) and PARTO with Gelfoam (100%). 31 Acutely bleeding gastric varices carry a high mortality with limited treatment options.…”
Section: Clinical Success and Survivalmentioning
confidence: 82%
See 2 more Smart Citations
“…For BRTO, PARTO, and CARTO, clinical success ranges from 91 to 100%, 90.6 to 100%, and 100%, respectively. 2,4,24,[27][28][29]31,38,39 Kim et al detected similar clinical success rates (defined as lack of variceal enhancement on postprocedural CT and cessation of bleeding on endoscopy) between BRTO with EO (93.9%) or STS (92%) and PARTO with Gelfoam (100%). 31 Acutely bleeding gastric varices carry a high mortality with limited treatment options.…”
Section: Clinical Success and Survivalmentioning
confidence: 82%
“…For BRTO, PARTO, and CARTO, this ranges from 79 to 100%, 94.7 to 100%, and 100%, respectively. 2,4,5,[27][28][29]31,38,39 In a recent retrospective study comparing BRTO and PARTO, Kim et al reported similar technical success rates of BRTO with EO (93.9%) or STS (92%), and PARTO with Gelfoam (100%). 31 Notably, the success rate of BRTO increases from 84-98% to 98-100% when used in conjunction with balloon-occluded antegrade transvenous obliteration (BATO), although combination therapies are beyond the scope of this article.…”
Section: Outcomes Technical Successmentioning
confidence: 92%
See 1 more Smart Citation
“…BRTO has a high efficacy in stopping acute gastric variceal bleeding and has shown to have a signifi cantly lower re-bleeding rate of gastric varices compared to tIPS or endoscopic treatment [9][10][11][12][13][14] . Recently, our group has shown the effectiveness of mBRtO using coils or vascular plugs in place of balloons [15][16][17] , which is comparable to conventional BRtO [8][9][10][11][12]18,19] . During the BRtO or mBRtO procedure, visualization of the gastric varices, feeding vessels, and its collaterals, is currently guided by 2D angiogram or digital subtraction angiogram.…”
Section: Introductionmentioning
confidence: 91%
“…The plug is also very useful in the occlusion of large portosystemic shunts that may cause refractory hepatic encephalopathy or bleeding from ectopic varices. [58][59][60] They can also be used in the treatment of congenital portocaval shunts such as the type 2 Abernethy malformations. [61][62][63] In the treatment of these congenital shunts that may produce congestive heart failure, another advantage of the device is that it can be deployed temporally and the hemodynamic effects of the shunt closure is evaluated, to see if acute shunt closure is well tolerated before final deployment.…”
Section: Portal and Mesenteric Venous Circulationmentioning
confidence: 99%